2016
DOI: 10.1177/0954407015618051
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the loading path for the tube-hydroforming process

Abstract: In general, hydroforming optimization aims to make a desired shape of a plastically deformed structure under dynamic forces. The automotive industry has shown great interest in tube hydroforming, which is a metal-forming process. The forces from the hydraulic fluid are utilized to deform a tube. The internal pressures and the axial feedings (of the axial forces) determine the quality of the deformed product. In this research, an optimization process is employed to evaluate the appropriate external forces but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…2, 68, 1012, 32–39 In the late 1990s, Choi et al 12 introduced the ESLM for linear dynamic response optimization, and the method has been expanded to various disciplines such as flexible multi-body dynamic systems, 34, 4042 rigid-body dynamic systems, 43 non-linear static systems, 10, 36, 37 and non-linear dynamic systems. 58, 11, 32, 33, 35, 39, 44, 45 Jeong et al 6 compared the ESLM and the response surface method with regard to the roof structure of a vehicle. Kim and Park 8 compared the ESLM and the conventional method subject to stress constraints.…”
Section: Non-linear Dynamic Response Structural Optimization and The mentioning
confidence: 99%
See 2 more Smart Citations
“…2, 68, 1012, 32–39 In the late 1990s, Choi et al 12 introduced the ESLM for linear dynamic response optimization, and the method has been expanded to various disciplines such as flexible multi-body dynamic systems, 34, 4042 rigid-body dynamic systems, 43 non-linear static systems, 10, 36, 37 and non-linear dynamic systems. 58, 11, 32, 33, 35, 39, 44, 45 Jeong et al 6 compared the ESLM and the response surface method with regard to the roof structure of a vehicle. Kim and Park 8 compared the ESLM and the conventional method subject to stress constraints.…”
Section: Non-linear Dynamic Response Structural Optimization and The mentioning
confidence: 99%
“…combination such as (M, S). In this example, the combinations of (M, S) are (2, 1), (4, 5), (5,8), (4,6), (6,7) and (5,7). The case of the combination (5, 8) is explained in detail using Figure 7.…”
Section: Side Structurementioning
confidence: 99%
See 1 more Smart Citation
“…2 In fact, hydroforming is the process of producing different parts of machines by applying fluid pressure. 3 This fluid usually, is oil or water. 4 Using the hydroforming process, it is possible to produce a tube component that its cross-section is varied along its axis.…”
Section: Introductionmentioning
confidence: 99%
“…Shinde et al investigated the effect of internal pressure, without axial feeding, on the success of tube hydroforming process numerically. 3 They analyzed the tube hydroformed in square cross- section die using LS-Dyna explicit solver. They found that the internal pressure that can cause the tube to burst can be determined using the Formation Limit Diagram (FLD).…”
Section: Introductionmentioning
confidence: 99%